Identification of Rainfall and Inundation pattern using remotely sensed data in Lake Sentarum Floodplain Area - Fajar Setiawan; Iwan Ridwansyah; Luki Subehi (Indonesian Society of Limnology, 2021)
Wetlands are vulnerable natural habitats that should be preserved to protect habitat for fish and wildlife, flood mitigation, improve water quality, recharge area, and maintain surface water flow during dry periods. Water bodies and swamp areas are two primary components of the wetland. Considering its essential roles for the ecosystem, Lake Sentarum was set as a national park area (Lake Sentarum National Park – TNDS), Indonesia's 15 national priority lakes, and; designated as a Ramsar site (The Convention on Wetlands) in Indonesia. Despite the significant roles for the ecosystem, providing the limnological characteristic of Lake Sentarum remains a challenge due to its remote location. This study aims to identify the rainfall and inundation characteristics in the Lake Sentarum area and develop the rainfall-inundation relationship in the TNDS area. First, we carried out rainfall analysis using the Climate Forecast System Reanalysis (CFSR) data. Second, we utilized a remote-sensing-based global surface water map from the Joint Research Centre (JRC) to describe the historical inundation pattern. Third, we applied the Normalized Different Water Index (NDWI) combined with Modification Normalized Different Water Index (MNDWI) to the selected Landsat dataset to extract the inundation area. Finally, we developed a rainfall-inundation relationship in the TNDS area. The result indicated that the yearly rainfall in the TNDS area has an increasing trend, with the highest peak in December and the second peak in April. Historical Landsat data shows that the TNDS has a complex pattern of inundation. The maximum water extent was 649 km2, with a 95 km2 as permanent (90>- 100 % water occurrence). These areas were constantly flooded, even in the dry season. The most significant non-permanent water was 161 km2 (80>- 90 % water occurrence). This permanent and larger temporary water area provides fish and other aquatic biotas habitats. It temporarily stores the water flowing slowly into the River Kapuas through the Tawang River. We captured the spatial inundation pattern and its relationship with the temporal regional rainfall. The developed relationship showed a lag of -60 days of accumulated rainfall correlated with the inundation area (R2 of 0.48, n=11). These findings will thus provide valuable data for lake managers and policy-makers to protect the biota and habitat in Lake Sentarum National Park area.